(untitled) (Journal of Pharmaceutical Negative Results, 2023)
In this article an endeavor has been made to highlight about ‘the Information needs and seeking behavior’ and related components at different institutions globally. This article carries out widely the literature survey as the purpose of the study. Different institutions are trying to find out the problems of the study through researchers, to get good quality information from the society’s development and quality knowledge. Various books, articles, journals, magazines, news papers, e-resources are giving the data to get a new information. Besides, research guides, teachers, information centers and many other sources are helping the researcher to perform a quality research. From one country to another the researcher are influenced to get an ‘information need and seeking behavior.’ Awareness programmes have given many new thoughts for the knowledge seekers in our society. Many institutes need information literacy program and library users program have conducted literacy of information awareness program which could be of help to library users as well as researchers for seeking information. Information literacy program will help to develop the users’ mentality to discover the fact of the knowledge and information. Researchers and professionals have to go in-depth in ‘information needs and seeking behavior and literacy information.’ Hence, this only will help to suggest the new researcher to find out the ‘information needs and seeking behavior’ globally.